Does The Use Of Social Network Service LINE Affect First-Year College Students’ Social Adjustment? - Elok Dianike Malay; Aulia Nataningsih (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2020)
This study examined the influence of social networking service (SNS) usage, especially LINE, on the first-year college students’ social adjustment in Indonesia. This correlational, non-experimental field study used an electronic questionnaire to measure 120 first-year college students’ social adjustment (using the Social Adjustment subscale of Student Adaptation to College Questionnaire/ SACQ) and data on LINE usage. Linear regression analysis showed that LINE usage affected students’ social adjustment. The number of actual friends in LINE and propensity to use LINE to collaborate with other students positively predicted social adjustment. On the other hand, the number of college friends in LINE did not contribute significantly to their social adjustment. These results give more evidence of the effect of SNS, especially LINE, on the first-year college students’ social adjustment in their campus. However, it is important to realize that SNS would give a beneficial effect if students could develop a real friendship and use it for collaborative activities.